Formulations with high glass transition temperatures for laminates

By adding organic particles and inorganic particles with core-shell structure to the epoxy resin, the problem of insufficient performance of CFRP molded parts in the prior art under high temperature conditions is solved, and a combination of high glass transition temperature and excellent impact strength is achieved.

CN114729157BActive Publication Date: 2025-04-25HENKEL KGAA
View PDF 23 Cites 0 Cited by

Patent Information

Application Number
CN202080080629.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-22
Filing Date
2020-11-19
Publication Date
2025-04-25
Estimated Expiration
2040-11-19

AI Technical Summary

Technical Problem

The prior art is difficult to produce carbon fiber reinforced plastic (CFRP) molded parts with high glass transition temperature and excellent impact strength in the automotive industry, especially at high temperature conditions.

Method used

By adding organic particles and inorganic particles having a core-shell structure to the epoxy resin, a resin composition can be formed, which can not only increase the glass transition temperature in the cured state, but also enhance the impact strength of the material.

Benefits of technology

It realizes the impact toughness of the material while maintaining a high glass transition temperature under high temperature conditions, and is suitable for molded parts in automotive structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003653663450000051
    Figure BDA0003653663450000051
  • Figure BDA0003653663450000071
    Figure BDA0003653663450000071
Patent Text Reader

Abstract

The present invention relates to a curable resin composition, a method for producing a cured composition using the curable resin composition, and articles, especially molded articles, produced by these methods.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to curable resin compositions, methods for producing cured compositions using the curable resin compositions, and articles, in particular moulded parts, produced by such methods.

[0002] Lightweight construction of vehicles is becoming increasingly important in the automotive industry. In particular, the automotive industry has an increasing demand for molded parts made of carbon fiber reinforced plastics (CFRP). For example, such molded parts are installed in the form of wheel rims, which are exposed to high temperatures during braking. Therefore, when producing corresponding molded parts, it is necessary to use a matrix resin that has a very high glass transition temperature T in the cured state. g , because otherwise a heat-resistant protective lacquer would have to be applied, which would make the production process even more complicated. In addition to the highest possible glass transition temperature, it is also important to equip the system with good impact strength in order to avoid microcracks that allow air to escape. However, a high glass transition temperature and good impact strength are opposite properties. Although it is known that cycloaliphatic epoxy resins cured with anhydrides lead to cured materials with high glass transition temperatures, many raw materials that increase the impact strength, such as plasticizers, lower the glass transition temperature of such matrix systems.

[0003] The present invention is based on the discovery of the inventors that by adding organic core-shell particles and inorganic particles, curable formulations based on epoxy resins can be obtained which have both a high glass transition temperature and excellent impact strength in the cured state.

[0004] The plastics materials obtainable in this way, in particular in the form of fiber-reinforced plastics molded parts, therefore exhibit advantageous mechanical properties and are therefore particularly suitable for use in automotive construction.

[0005] Therefore, in a first aspect, the present invention relates to a resin composition comprising at least one epoxy resin component and at least one curing component, characterized in that, based on the total weight of the resin composition, the resin composition comprises:

[0006] (A) 1-30 wt% of particles having a core-shell structure, and

[0007] (B) 1-10 wt% of inorganic particles.

[0008] Another aspect of the present invention provides a method for producing a curing composition, comprising the steps of:

[0009] (1) providing a resin composition as described herein; and

[0010] (2) Curing the resin composition to obtain a cured composition.

[0011] In another aspect, the present invention relates to a cured composition obtainable according to the process described herein.

[0012] As used herein, "at least one" refers to 1 or more, e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9 or more. When related to the components of the catalyst compositions described herein, the statement does not refer to the absolute number of molecules, but rather to the type of component. Thus, "at least one epoxide" means, for example, one or more different epoxides, i.e., one or more different types of epoxides. Together with the stated amounts, the stated amounts refer to the total amount of the component of the corresponding specified type as defined above.

[0013] The viscosity of the liquid composition described herein is particularly low, sufficient to make the composition pumpable and capable of wetting and impregnating fiber materials, for example, as used for fiber-reinforced plastic parts. In various embodiments, the reaction mixture has a viscosity of less than 100 mPas at a temperature of 100° C. For the determination of viscosity, the resin mixture is prepared at room temperature using a suitable mixer and the viscosity is measured on a plate / plate rheometer with a diameter of 25 mm and a gap of 0.05 mm, rotating at a shear rate of 100 revolutions per second, with a heating rate of 6 K / min.

[0014] The present invention relates to a resin composition comprising at least one epoxy resin component and at least one curing component, and is characterized in that it also comprises other organic particles and inorganic particles with a core-shell structure.

[0015] The organic particles with a core-shell structure are preferably rubber particles. The rubber particles with a core-shell structure can be any particle material having a rubber core that is known and suitable for the purposes described herein. The glass transition temperature T of the rubber core is g Preferably below -25°C, more preferably below -50°C, even more preferably below -70°C. g Even well below -100°C. Core-shell particles also have T g A shell portion of at least 50°C is preferred.

[0016] Here, "core" refers to the inner part of the particle. The core can represent the center of the core-shell particle or the inner sheath or domain of the particle. "Sheath" or "shell" refers to the part outside the core that usually forms the shell, i.e. the outermost part of the particle. The shell material is preferably grafted onto the core or crosslinked with the core. The rubber core can constitute 50 to 95% by weight, in particular 60 to 90% by weight of the particle.

[0017] The core of the particle can be a polymer or copolymer of a conjugated diene such as butadiene or a lower alkyl acrylate (such as n-butyl acrylate, ethyl acrylate, isobutyl acrylate or 2-ethylhexyl acrylate). The core polymer may additionally contain up to 20% by weight of other copolymerized monounsaturated monomers such as styrene, vinyl acetate, vinyl chloride and methyl methacrylate, etc. The core polymer is optionally crosslinked. In certain embodiments, the core polymer contains up to 5% by weight of a copolymerized graft monomer, and the copolymerized graft monomer contains two or more unsaturated bonds with different reactivities, such as diallyl maleate, monoallyl fumarate and allyl methacrylate, etc., wherein at least one of the unsaturated bonds is not conjugated.

[0018] The core polymer may also be a silicone rubber. The glass transition temperature of these materials is generally below -100°C. Core-shell particles having such a silicone rubber core include those commercially available from Wacker Chemie (Munich, Germany) under the trade name Genioperl.

[0019] The shell polymer optionally grafted onto the core or crosslinked with the core is preferably a polymer of a lower alkyl methacrylate such as methyl methacrylate, ethyl methacrylate or tert-butyl methacrylate. Homopolymers of such methacrylates may be used. In addition, up to 40% by weight of the shell polymer may be formed from other vinyl monomers such as styrene, vinyl acetate, vinyl chloride, methyl acrylate, ethyl acrylate and butyl acrylate. The molecular weight of the grafted shell polymer is typically 20,000 to 500,000.

[0020] The rubber particles generally have an average particle size of about 0.03 to about 2 microns or about 0.05 to about 1 micron. In certain embodiments of the present invention, the rubber particles have an average diameter less than about 500nm. In other embodiments, the average particle size is less than about 200nm. For example, the core-shell rubber particles can have an average diameter in the range of about 25 to about 200nm or about 50 to 150nm.

[0021] Methods for making rubber particles having a core-shell structure are well known in the art and are described, for example, in U.S. Pat. Nos. 3,985,703, 4,180,529, 4,315,085, 4,419,496, 4,778,851, 5,223,586, 5,290,857, 5,534,594, 5,686,509, 5,789,482, 5,981,659, 6,111,015, 6,147,142 and 6,180,693, 6,331,580 and 2005 / 124,761.

[0022] Core-shell particles can have reactive groups in the shell polymer, and the reactive groups can react with epoxy resin or epoxy resin curing agent. For example, glycidyl is suitable. Particularly preferred core-shell particles are those described in European patent application EP 1632533 A1. The core-shell particles described therein include crosslinked rubber cores (in most cases a crosslinked copolymer of butadiene) and preferably a shell of a copolymer of styrene, methyl methacrylate, glycidyl methacrylate and optionally present acrylonitrile.

[0023] In various embodiments, core-shell particles as described in WO 2007 / 025007 are used.

[0024] Also as described in the document cited above, the rubber particles with core-shell structure are preferably dispersed in polymer or epoxy resin.Preferred core-shell particles include those available from Kaneka Corporation under the name Kaneka Kane Ace, including Kaneka Kane Ace 15 and 120 product lines, including Kaneka Kane Ace MX 153, KanekaKane Ace MX 156, Kaneka Kane Ace MX 257 and Kaneka Kane Ace MX 120 core-shell particle dispersions and their mixtures.These products comprise the core-shell rubber particles pre-dispersed in the epoxy resin with a concentration of about 33% or 25%.

[0025] The resin composition according to the invention preferably comprises a total amount of 1% to 30% by weight, in particular 15 to 25% by weight, of core-shell particles, based in each case on the total weight of the resin composition and the core-shell particles themselves, i.e. without any possible dispersion medium present.

[0026] The composition according to the invention further comprises inorganic particles. Suitable inorganic particles have a particle size in the range of 20 to 400 nm, in particular in the range of 20 to 300 nm and even more preferably in the range of 20 to 250 nm.

[0027] According to some embodiments, the inorganic particles are inorganic silica particles. Suitable inorganic particles are commercially available, for example, from Evonik under the name Nanopox.

[0028] The resin composition according to the invention preferably comprises inorganic particles in a total amount of 1% to 10% by weight, in particular 4% to 8% by weight, based in each case on the total weight of the resin composition.

[0029] According to some embodiments, the total amount of organic particles (A) and inorganic particles (B) in the resin composition according to the invention is in the range of 1 to 30 wt. %, preferably in the range of 15 to 25 wt. %, in each case based on the total weight of the resin composition.

[0030] According to the present invention, the resin composition further comprises at least one epoxy resin component. Suitable epoxy resin components include one or more epoxy compounds as described below.

[0031] In the context of the present invention, epoxy resins may include monomers, prepolymers and polymers containing epoxy groups and mixtures thereof, and are also referred to hereinafter as epoxide-containing or epoxy-containing resins. Suitable epoxy-containing resins are in particular resins having 1 to 10, preferably 2 to 10 epoxy groups per molecule. As used herein, "epoxy" refers to 1,2-epoxy (oxirane type).

[0032] The epoxy resins useful herein may vary and include conventional commercially available epoxy resins, each of which may be used alone or in combinations of two or more different epoxy resins. In selecting an epoxy resin, not only the properties of the final product, but also the properties of the epoxy resin such as viscosity and other properties that affect processability are important.

[0033] The epoxide equivalent weight of the polyepoxides may vary between 75 and 50,000, preferably between 170 and 5,000. In principle, the polyepoxides may be saturated, unsaturated, cyclic or acyclic, aliphatic, cycloaliphatic, aromatic or heterocyclic polyepoxide compounds.

[0034] According to some embodiments, the at least one epoxy resin component includes a cycloaliphatic epoxy resin.

[0035] Examples of suitable cycloaliphatic epoxides are compounds having a saturated hydrocarbon ring with epoxide oxygen atoms attached to two adjacent carbon atoms of the carbon ring, as shown in the following formula:

[0036]

[0037] Wherein R is a linking group and n is an integer from 2 to 10, preferably from 2 to 4, even more preferably from 2 to 3. When n is 2 or greater, these compounds are diepoxides or polyepoxides. Such cycloaliphatic epoxy resins may have an epoxide equivalent weight of about 95 to 250, in particular 100 to 150. Mixtures of monoepoxides, diepoxides and / or polyepoxides may be used.

[0038] Other examples of suitable cycloaliphatic epoxides are in particular epoxides of cycloaliphatic esters of dicarboxylic acids, such as bis-(3,4-epoxycyclohexylmethyl oxalate), bis-(3,4-epoxy-cyclohexylmethyl adipate), bis-(3,4-epoxy-6-methylcyclohexylmethyl adipate) and bis-(3,4-epoxycyclohexylmethyl pimelate). Other suitable diepoxides of cycloaliphatic esters are described, for example, in US-A-2750395.

[0039] Other suitable cycloaliphatic epoxides are, for example, 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, bis-(3,4-epoxycyclohexyl adipate) and 3,4-epoxy-1-methylcyclohexylmethyl 3,4-epoxy-1-methylcyclohexanecarboxylate. Other suitable cycloaliphatic epoxides are described, for example, in US Pat. No. 2,890,194.

[0040] According to some embodiments, the at least one epoxy resin component includes an epoxy compound selected from the group consisting of bis-(3,4-epoxycyclohexylmethyl oxalate), bis-(3,4-epoxycyclohexylmethyl adipate), bis-(3,4-epoxy-6-methylcyclohexylmethyl adipate), bis-(3,4-epoxycyclohexylmethyl pimelate), 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, bis-(3,4-epoxycyclohexyl adipate), 3,4-epoxy-1-methylcyclohexanecarboxylate, and mixtures thereof.

[0041] Other examples of polyepoxides suitable for the resin composition according to the invention include, for example, polyglycidyl ethers prepared by reacting epichlorohydrin or epibromohydrin with polyphenols in the presence of a base. Suitable polyphenols for this are, for example, resorcinol, catechol, hydroquinone, bisphenol A (bis-(4-hydroxy-phenyl)-2,2-propane), bisphenol F (bis(4-hydroxyphenyl)methane), bis(4-hydroxyphenyl)-1,1-isobutane, 4,4'-dihydroxybenzophenone, bis(4-hydroxyphenyl)-1,1-ethane and 1,5-hydroxynaphthaline. Other polyphenols suitable as the basis for the polyglycidyl ethers are the condensation products of phenols of the known phenol-formaldehyde resin type with formaldehyde or acetaldehyde.

[0042] Other polyepoxides that are suitable in principle are polyglycidyl ethers of polyols or diamines. These polyglycidyl ethers are derived from polyols such as ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,4-butanediol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol or trimethylolpropane.

[0043] Other polyepoxides are polyglycidyl esters of polycarboxylic acids, for example reaction products of glycidol or epichlorohydrin with aliphatic or aromatic polycarboxylic acids, such as oxalic acid, succinic acid, glutaric acid, terephthalic acid or dimerized fatty acids.

[0044] Other suitable epoxy resins are known in the art and can be found, for example, in Lee H. & Neville, K., Handbook of Epoxy Resins, McGraw-Hill Book Company, 1982 (reprint edition).

[0045] Other epoxides are derived from the epoxidation products of olefinically unsaturated alicyclic compounds or from natural oils and fats.

[0046] Depending on the intended use, the composition may preferably additionally comprise a toughening resin. This may also be an epoxy resin. Carboxyl-terminated butadiene-acrylonitrile copolymers (CTBN) and adducts of liquid epoxy resins based on diglycidyl ethers of bisphenol A can be used as toughening epoxy resins, and these adducts are known per se. A specific example is the reaction product of Hycar CTBN 1300X8, 1300X13 or 1300X15 (from BFGoodrich) with a liquid epoxy resin. In addition, the reaction product of amino-terminated polyalkylene glycols (Jeffamine) can also be used with an excess of liquid polyepoxides. In principle, according to the present invention, the reaction product of a mercapto-functional prepolymer or a liquid Thiokol polymer can also be used as a toughening epoxy resin together with an excess of polyepoxides. However, the reaction product of polymerized fatty acids, particularly dimer fatty acids, and epichlorohydrin, glycidol or particularly diglycidyl ethers of bisphenol A (DGBA) is very particularly preferred.

[0047] The resin composition according to the invention further comprises at least one curing component.

[0048] According to some embodiments, the at least one curing component includes at least one anhydride curing agent.

[0049] An example of a suitable anhydride-based curing agent is a norbornene-based dicarboxylic anhydride. Suitable norbornene-based dicarboxylic anhydride is represented by the following formula:

[0050]

[0051] wherein each R independently represents a hydrocarbon group, a halogen or an inert substituted hydrocarbon group; z is an integer from 0 to 8, preferably an integer from 0 to 2, and especially an integer from 0 to 1; R 2, if present, represents an alkyl group, preferably a methyl group. As used herein, the term "inertly substituted" means that the substituents do not adversely affect the ability of the anhydride group to react with the epoxy resin and cure the epoxy resin. In the case where z is 1 or greater, preferably at least one R 2 The group is bonded to the carbon atom in position 5. In the dicarboxylic anhydride based on norbornene, the dicarboxylic anhydride group can be in the exo conformation or the endo conformation. In the context of the present invention, both isomers and mixtures of both isomers are suitable in principle. Preferred examples of dicarboxylic anhydrides based on norbornene as described herein are bicyclo[2.2.1]-5-heptene-2,3-dicarboxylic anhydride, i.e. an anhydride having the above structure in which z is 0, and bicyclo[2.2.1]-methylhept-5-ene-2,3-dicarboxylic anhydride, i.e. an anhydride in which R 2 is a methyl group (the methyl group is preferably bonded to the carbon atom at position 5) and z is 1, and has an anhydride of the above structure. According to some embodiments, the at least one curing component of the resin composition described herein comprises at least one anhydride curing agent, and the at least one anhydride curing agent is selected from bicyclo [2.2.1] -5-heptene-2,3-dicarboxylic anhydride, bicyclo [2.2.1] -methylhept-5-ene-2,3-dicarboxylic anhydride and mixtures thereof. Other suitable anhydride-based curing agents are saturated norbornene-based dicarboxylic anhydrides. These are derived from the above structure, wherein the double bonds in the norbornene skeleton are hydrogenated.

[0052] Other anhydride curing agents are aliphatic anhydrides such as hexahydrophthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride and mixtures thereof; and aromatic anhydrides such as phthalic anhydride, trimellitic anhydride and mixtures thereof. Particularly suitable anhydride curing agents are hexahydrophthalic anhydride, methylhexahydrophthalic anhydride and mixtures thereof. Other suitable anhydride curing agents are copolymers of styrene and maleic anhydride and other anhydrides copolymerizable with styrene.

[0053] According to a preferred embodiment, the at least one curing component of the resin composition described herein comprises at least one anhydride curing agent selected from hexahydrophthalic anhydride, methylhexahydrophthalic anhydride and mixtures thereof.

[0054] Guanidine, substituted guanidine, substituted urea, melamine resin, guanamine derivatives, cyclic tertiary amines, aromatic amines and / or mixtures thereof can be used as heat-activatable or latent curing agents. In this case, the curing agent can participate in the curing reaction in a stoichiometric manner. However, they may also have a catalytic effect. Examples of substituted guanidines are methylguanidine, dimethylguanidine, trimethylguanidine, tetramethylguanidine, methylisobiguanide, dimethylisobiguanide, tetramethylisobiguanide, hexamethylisobiguanide, heptamethylisobiguanide, and more particularly cyanoguanidine (dicyandiamide). Representatives of guanamine derivatives that can be mentioned include alkylated benzoguanamine resins, benzoguanamine resins or methoxymethyl-ethoxymethylbenzoguanamine. For single-component heat-cured moldings, the selection criteria are that these substances have low solubility in the resin system at room temperature, so that in this case, solid finely ground curing agents are preferred. Dicyandiamide is particularly suitable. This ensures good storage stability of the heat-curable molding.

[0055] As a supplement or alternative to the above-mentioned curing agents, catalytic substituted ureas can be used. These substituted ureas are especially p-chlorophenyl-N,N-dimethylurea (monuron), 3-phenyl-1,1-dimethylurea (fenuron) or 3,4-dichlorophenyl-N,N-dimethylurea (diuron). In principle, catalytic acrylic tertiary amines or alkyl tertiary amines such as benzyldimethylamine, tris(dimethylamino)phenol, piperidine or piperidine derivatives can also be used. However, these are usually too soluble in the adhesive system, making the one-component system unsuitable for storage stability. In addition, various preferred solid imidazole derivatives can be used as catalytic promoters. Representative examples include 2-ethyl-2-methylimidazole, N-butylimidazole, benzimidazole and NC 1-12 -alkylimidazoles or N-arylimidazoles. Particularly preferred is the use of a combination of a curing agent called accelerated dicyandiamide in finely ground form and an accelerator. This means that the separate addition of an accelerator which has a catalytic effect on the epoxy curing system is superfluous.

[0056] The composition according to the invention can also be formulated as a two-component composition, in which the two reaction components are mixed with one another only shortly before application and then cured at room temperature or at moderately elevated temperatures. The reaction components known per se for two-component epoxy compositions can be used as the second reaction component, for example diamines or polyamines, amino-terminated polyalkylene glycols (e.g. Jeffamine, amino-poly-THF) or polyaminoamides. Further reactive partners can be mercapto-functional prepolymers, such as liquid Thiokol polymers, and the epoxy composition according to the invention can also be cured in a 2K formulation, preferably with carboxylic anhydrides as the second reaction component.

[0057] The present invention also relates to a method for producing a cured composition, comprising the steps of: (1) providing a resin composition as described herein; and (2) curing the resin composition to obtain a cured composition.

[0058] Accordingly, the cured composition has increased mechanical stability, in particular increased impact toughness, without reducing the glass transition temperature, so that the resulting composition can be exposed to elevated temperatures during manufacture and its intended use. The polyol is therefore particularly suitable for the production of fiber-reinforced plastic molded parts, such as automotive parts.

[0059] As used herein, "providing" refers to mixing the components of resin combination in any order. For example, before adding the remaining ingredients, it may be advantageous to first combine two or more ingredients and optionally mix the ingredients to form a heterogeneous or homogeneous mixture. For example, the at least one epoxy resin component can be first mixed with organic and / or inorganic particles, and then, for example, shortly before solidification, the at least one curing component can be added and mixed into other well-mixed ingredients. Between various combinations and mixing steps, it may be advantageous to cool the reaction mixture to room temperature. In another embodiment, it may be advantageous to heat the reaction mixture between various combinations and mixing steps to improve solubility.

[0060] Usually, each component of resin combination can be used by itself or as a solution in a solvent such as an organic solvent or an organic solvent mixture. For this purpose, any known solvent suitable for the purpose according to the present invention can be used. For example, the solvent can be a high boiling point organic solvent. The solvent can be selected from oil, benzene, toluene, xylene, ethylbenzene and their mixture.

[0061] The resin compositions described herein may be combined with other ingredients known in the art in the form of adhesive compositions or injection resins.

[0062] Adhesive compositions or injection resins of this type may contain a number of other components, all of which are known to those skilled in the art, including but not limited to frequently used auxiliaries and additives, such as fillers, plasticizers, reactive and / or non-reactive diluents, mobile solvents, coupling agents (e.g. silanes), mold release agents, adhesion promoters, wetting agents, adhesives, flame retardants, wetting agents, thixotropic agents and / or rheological agents (e.g. pyrogenic silica), aging and / or corrosion inhibitors, stabilizers and / or dyes. Depending on the requirements of the adhesive or injection resin and its use and taking into account aspects of production, flexibility, strength and adhesion to the substrate, the auxiliaries and additives are incorporated into the composition in different amounts.

[0063] In a preferred embodiment, the composition of the present invention contains no plasticizers, or contains less than 0.1% by weight of plasticizers, since these plasticizers tend to reduce Tg .

[0064] In various embodiments of the present invention, according to the desired use, the resin combination is applied to the substrate, for example, when used as an adhesive, or when used as a molding material for the production of plastic parts, it is filled into a mold. In a preferred embodiment, the method is a transfer molding (RTM) method and the resin combination is a reactive injection resin. "Reactivity" used in this article refers to the fact that the injection resin is chemically crosslinkable. In the RTM method, a resin combination is provided, i.e. the step (1) of the method, which may include filling the injection resin, particularly injecting it into a mold. In the production of fiber-reinforced plastic parts to which the method and the reaction mixture are particularly suitable, fibers or semi-finished fiber products (prewoven fabrics / preforms (prewovens / preforms)) may be placed in a mold before being injected into the mold. Materials known in the prior art for this application, particularly carbon fibers, may be used as fibers and / or semi-finished fiber products.

[0065] In various embodiments, the resin composition is an adhesive composition or an injection resin. The injection resin is preferably pumpable and is particularly suitable for transfer molding (RTM method). Therefore, in various embodiments, the reaction mixture has a viscosity of <100 mPas at a temperature of 100° C. (i.e., a typical infusion temperature).

[0066] Therefore, in one embodiment, the present invention also relates to a molded part obtainable in an RTM process by means of the resin system according to the invention. The RTM process in which the resin system can be used is known per se in the prior art and can be easily adapted by a person skilled in the art so that the reaction mixture according to the invention can be used.

[0067] The open time of the resin composition as described herein is preferably greater than 90 seconds and preferably in the range of 2 to 5 minutes, in particular about 3 minutes. As used herein, "about" in relation to a numerical value refers to the numerical value ± 10%.

[0068] The resin composition in step (2) of the method according to the present invention can be cured at different reaction temperatures, depending on the type of epoxide and curing agent used and the purpose of the curing composition. Thus, the curing temperature can be from 70°C to 280°C.

[0069] The curing process can generally be carried out at elevated temperatures, i.e. >25° C. The resin is preferably cured at 80° C. to 280° C., more preferably at 100° C. to 240° C. The duration of the curing process also depends on the resin to be cured and the catalyst composition and can be between 0.01 hours and 10 hours. The curing cycle preferably lasts a few minutes, i.e. in particular 1 to 15 minutes. The curing process can also be carried out in one or more steps.

[0070] In some embodiments, the resin composition described herein is cured in a one-step process at a temperature of 100°C to 240°C, preferably 160°C to 240°C, more preferably 180°C to 240°C, for 0.01 to 10 hours, preferably 0.1 to 5 hours, more preferably 1 hour.

[0071] In an alternative embodiment, the resin composition as described herein can be cured in a multi-step process. This multi-step process includes a first step of pre-curing, the resin composition is pre-cured at a temperature of 110°C to 200°C, preferably 130°C to 190°C, more preferably 180°C for 0.1 to 3 hours, preferably 0.5 to 2 hours, more preferably 1 hour, and then post-cured in a second step. The second step of post-curing can include one or more sub-steps, so that the pre-cured resin composition is post-cured at least once, preferably at least twice, more preferably at least three times, in each case at a temperature of 110°C to 260°C, preferably 130°C to 190°C, more preferably 180°C, in each case for 0.1 to 3 hours, preferably 0.5 to 2 hours, more preferably 1 hour. For example, such a second curing step may include post-curing the pre-cured resin composition at a temperature of 130°C to 230°C, preferably 180°C to 220°C, more preferably 200°C, for 0.1 to 3 hours, preferably 0.5 to 2 hours, more preferably 1 hour; then post-curing at a temperature of 150°C to 250°C, preferably 190°C to 230°C, more preferably 220°C, for 0.1 to 3 hours, preferably 0.5 to 2 hours, more preferably 1 hour; then post-curing at a temperature of 170°C to 260°C, preferably 200°C to 250°C, more preferably 240°C, for 0.1 to 3 hours, preferably 0.5 to 2 hours, more preferably 1 hour.

[0072] The resin cured as described herein preferably has a critical stress intensity factor K1c of ≥0.8, preferably ≥0.9, more preferably ≥0.95 and most preferably ≥1.0. In various embodiments, the glass transition temperature of the cured resin is in the range of ≥250°C, in particular ≥255°C, and typically in the range of up to 300°C. The elastic modulus of the cured resin is preferably at least 2,000 N / mm 2 , more preferably at least 2,100 N / mm 2, usually between 2,200 and 5,000 N / mm 2 within the range.

[0073] Furthermore, the present invention relates to a cured composition obtainable according to the process described herein. Depending on the process, the composition can be present as a molded part, in particular as a fiber-reinforced plastic molded part. Such molded parts are preferably used in automotive construction or aerospace.

[0074] The curing compositions are therefore particularly suitable as matrix resins for fiber composite materials. These can be used in various application methods, such as resin transfer molding (RTM) or infusion.

[0075] Known high-performance fiber materials are suitable as fiber components for fiber composite materials. For example, these can be composed of glass fibers; synthetic fibers such as polyester fibers, polyethylene fibers, polypropylene fibers, polyamide fibers, polyimide fibers or aramid fibers; carbon fibers; boron fibers; oxide or non-oxide ceramic fibers such as aluminum oxide / silicon dioxide fibers, silicon carbide fibers; metal fibers, for example made of steel or aluminum; or natural fibers such as flax, hemp or jute. The fibers can be incorporated in the form of mats, woven fabrics, knitted fabrics, nonwoven fabrics, fiber webs or rovings. Two or more of these fiber materials can also be used as a mixture. Chopped fibers can be selected, but preferably synthetic long fibers, in particular woven and nonwoven fabrics, are used. Such high-strength fibers, nonwoven fabrics, woven fabrics and rovings are known to those skilled in the art.

[0076] In particular, the fiber composite material should contain more than 40% by volume, preferably more than 50% by volume, particularly preferably 50 to 70% by volume of fibers, based on the total fiber composite material, in order to obtain particularly good mechanical properties. In the case of carbon fibers, the volume percentage is determined according to standard DIN EN 2564:1998-08, in the case of glass fibers, according to standard DIN EN ISO 1172:1998-12.

[0077] Such fiber composite materials are particularly suitable as automotive components. Compared to steel, such fiber composite materials have several advantages, namely they are lighter and are characterized by a higher resistance to crushing and are more durable.

[0078] Furthermore, it goes without saying that all embodiments which have been disclosed above in connection with the method can also be used in the same way for the resin system and the curing composition, and vice versa. Example

[0079] Example Formulation 1

[0080] Epoxy resin components:

[0081] 97.7 g of cycloaliphatic epoxy resin with 30% organic core-shell particles

[0082] 4.1g organic core-shell structure particles

[0083] 42.5g has 40% SiO 2 Granular cycloaliphatic epoxy resin

[0084] 3.0g multifunctional fatty acid ester (release agent)

[0085] Curing components:

[0086] 132.0 g mixture of bicyclo[2.2.1]-5-heptene-2,3-dicarboxylic anhydride and bicyclo[2.2.1]methylhept-5-ene-2,3-dicarboxylic anhydride

[0087] 2.0g 1-Methylimidazole

[0088] The epoxy resin component and the curing component were homogenized and then poured into a steel mold. Pre-curing was carried out at 130°C for 30 minutes. The mixture was then post-cured at 180°C for 1 hour, at 200°C for 1 hour, at 220°C for 1 hour and finally at 240°C for 1 hour. The mixture was post-cured at 180°C for one hour to ensure complete cross-linking. In this way, polymer plates of approximately 4 mm thickness and an area of ​​20 cm x 20 cm were produced.

[0089] The total amount of organic particles is about 12%; the total amount of inorganic particles is about 6%. The physical properties of the panels produced in this way are clearly summarized in the table below.

[0090] Table 1: Physical properties of Example Composition 1

[0091] Flexural modulus [MPa] 2,159 Flexural strength[MPa] 96 K1c[MPa*m1 / 2] 1.0 Tg DMA tan delta[℃] 280 Tg DMA E' initial [℃] 255

[0092] Example Formulation 2

[0093] Epoxy resin components:

[0094] 81.6 g of cycloaliphatic epoxy resin with 30% core-shell structure particles

[0095] 3.4g core-shell structure particles

[0096] 60.0g with 40% SiO 2 Granular cycloaliphatic epoxy resin

[0097] 3.0g multifunctional fatty acid ester (release agent)

[0098] Curing components:

[0099] 132.0 g mixture of bicyclo[2.2.1]-5-heptene-2,3-dicarboxylic anhydride and bicyclo[2.2.1]methylhept-5-ene-2,3-dicarboxylic anhydride

[0100] 2.0g 1-Methylimidazole

[0101] The epoxy resin component and the curing component were homogenized and then poured into a steel mold. Pre-curing was carried out at 130°C for 30 minutes. The mixture was then post-cured at 180°C for 1 hour, at 200°C for 1 hour, at 220°C for 1 hour and finally at 240°C for 1 hour to ensure complete cross-linking. In this way, polymer plates of approximately 4 mm thickness and an area of ​​20 cm x 20 cm were produced.

[0102] The total amount of organic particles is about 10%; the total amount of inorganic particles is about 8%. The physical properties of the panels produced in this way are clearly summarized in the table below.

[0103] Table 2: Physical properties of Example Composition 2

[0104] Flexural modulus [MPa] 2,400 Flexural strength[MPa] 96 K1c[MPa*m1 / 2] 0.9 Tg DMA tan delta[℃] 275 Tg DMA E' initial [℃] 250

[0105] Comparative Example

[0106] Epoxy resin components:

[0107] 137.0 g of cycloaliphatic epoxy resin with 30% core-shell structure particles

[0108] 3.0g multifunctional fatty acid ester (release agent)

[0109] Curing components:

[0110] 137.0 g mixture of bicyclo[2.2.1]-5-heptene-2,3-dicarboxylic anhydride and bicyclo[2.2.1]methylhept-5-ene-2,3-dicarboxylic anhydride

[0111] 2.0g 1-Methylimidazole

[0112] The epoxy resin component and the curing component were homogenized and then poured into a steel mold. Pre-curing was carried out at 130°C for 30 minutes. The mixture was then post-cured at 180°C for 1 hour, at 200°C for 1 hour, at 220°C for 1 hour and finally at 240°C for 1 hour to ensure complete cross-linking. In this way, polymer plates of approximately 4 mm thickness and an area of ​​20 cm x 20 cm were produced.

[0113] The total amount of organic particles is about 15%. The physical properties of the panels produced in this way are clearly summarized in the table below.

[0114] Table 3: Physical properties of the comparative compositions

[0115] Flexural modulus [MPa] 2,182 Flexural strength[MPa] 79 K1c[MPa*m1 / 2] 0.7 Tg DMA tan delta[℃] 281 Tg DMA E' initial [℃] 252

[0116] A direct comparison of the two example formulations 1 and 2 according to the invention with the comparative example formulation shows that the combination of organic core-shell particles and inorganic particles in the cycloaliphatic epoxy resin composition leads to an increase in the K1c value without a decrease in the glass transition temperature of the cured composition.

Claims

1. A resin composition comprising at least one epoxy resin component and at least one curing component, characterized in that: Based on the total weight of the resin composition, the resin composition comprises: (A) 10 to 30% by weight of particles having a core-shell structure, and (B) 6 to 10% by weight of inorganic particles, wherein the inorganic particles are inorganic silica particles, wherein the at least one epoxy resin component comprises a cycloaliphatic epoxy resin; wherein the at least one curing component comprises at least one anhydride curing agent selected from the group consisting of bicyclo[2.2.1]-5-heptene-2,3-dicarboxylic anhydride, bicyclo[2.2.1]methylhept-5-ene-2,3-dicarboxylic anhydride, and mixtures thereof; and Therein, the total amount of particles (A) and particles (B) is in the range of 18 to 30% by weight, based on the total weight of the resin composition in each case.

2. The resin composition according to claim 1, characterized in that: (a) the total amount of particles (A) and particles (B) is in the range of 18 to 25% by weight, in each case based on the total weight of the resin composition; and / or (b) the amount of inorganic particles (B) is in the range of 6 to 8 wt %; and / or (c) Particles (A) and particles (B) are contained in the epoxy resin component.

3. The resin composition according to claim 1 or 2, characterized in that The at least one epoxy resin component is an epoxy compound selected from the following: bis-(3,4-epoxycyclohexylmethyl oxalate), bis-(3,4-epoxycyclohexylmethyl adipate), bis-(3,4-epoxy-6-methylcyclohexylmethyl adipate), bis-(3,4-epoxycyclohexylmethyl pimelate), 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, bis-(3,4-epoxycyclohexyl adipate), 3,4-epoxy-1-methylcyclohexanecarboxylate and mixtures thereof.

4. A method for producing a cured composition comprising the steps of: (1) providing a resin composition according to any one of claims 1 to 3; and (2) Curing the resin composition to obtain a cured composition.

5. The method according to claim 4, characterized in that The method is transfer molding, and the resin composition is a reactive injection resin.

6. The method according to claim 4 or 5, characterized in that Step (1) comprises injecting the resin composition into a mold in which the fiber or semi-finished fiber product is placed.

7. The method according to claim 6, characterized in that Step (1) comprises injecting the resin composition into a mold in which the prewoven fabric / preform is placed.

8. The method according to claim 4 or 5, characterized in that: (a) in step (2), the resin composition is cured at a temperature of 100° C. to 240° C. for 0.01 to 10 hours; or (b) In step (2), the resin composition is first pre-cured at a temperature of 70°C to 150°C for 0.1 hour to 3 hours and then post-cured at least once, in each case at a temperature of 110°C to 260°C, for 0.1 hour to 3 hours in each case.

9. The method according to claim 8, characterized in that: (a) In step (2), the resin composition is cured at a temperature of 160°C to 240°C.

10. The method according to claim 9, characterized in that: (a) In step (2), the resin composition is cured at a temperature of 180°C to 240°C.

11. The method according to claim 8, characterized in that: (a) In step (2), the resin composition is cured for 0.1 to 5 hours.

12. The method according to claim 11, characterized in that: (a) In step (2), the resin composition is cured for 1 hour.

13. The method according to claim 8, characterized in that: (b) In step (2), the resin composition is first pre-cured at a temperature of 100°C to 140°C.

14. The method according to claim 13, characterized in that: (b) In step (2), the resin composition is first pre-cured at a temperature of 130°C.

15. The method according to claim 8, characterized in that: (b) In step (2), the resin composition is first pre-cured for 0.5 hour to 2 hours.

16. The method according to claim 15, characterized in that: (b) In step (2), the resin composition is first pre-cured for 0.5 hours.

17. The method according to claim 8, characterized in that: (b) In step (2), the resin composition is then post-cured at least twice.

18. The method according to claim 17, characterized in that: (b) In step (2), the resin composition is then post-cured at least three times.

19. The method according to claim 8, characterized in that: (b) In step (2), the resin composition is then post-cured at a temperature of 130° C. to 190° C. in each case.

20. The method according to claim 19, characterized in that: (b) In step (2), the resin composition was then post-cured at a temperature of 180° C. in each case.

21. The method according to claim 8, characterized in that: (b) In step (2), the resin composition is then post-cured for in each case 0.5 hour to 2 hours.

22. The method according to claim 21, characterized in that: (b) In step (2), the resin composition was then post-cured for in each case 1 hour.

23. A cured composition obtainable by a process according to any one of claims 4 to 22.

24. The curing composition according to claim 23, characterized in that The cured composition has a K1c value of at least 0.

8.

25. The curing composition according to claim 23 or 24, characterized in that The glass transition temperature T of the cured composition g ≥250℃.

26. The curing composition according to claim 23 or 24, characterized in that The cured composition is a molded part.

27. The curing composition according to claim 26, characterized in that The cured composition is a fiber reinforced molded part.

Citation Information

Patent Citations

  • Process for producing modified epoxy resin

    EP1632533A1

  • Core-shell structured silicone rubber graft polymers, impact-resistant modified molding compounds and molded bodies and method for producing the same

    US20050124761A1

  • Diepoxides

    US2750395A

  • Compositions of epoxides and polycarboxylic acid compounds

    US2890194A

  • Process for manufacture of acrylic core / shell polymers

    US3985703A